Increased heroin intake and relapse vulnerability in intermittent relative to continuous self‐administration: Sex differences in rats. (9th February 2022) - D'Ottavio, Ginevra; Reverte, Ingrid; Ragozzino, Davide; Meringolo, Maria; Milella, Michele Stanislaw; Boix, Fernando; Venniro, Marco; Badiani, Aldo; Caprioli, Daniele
Abstract : Background and Purpose: Studies using intermittent‐access drug self‐administration show increased motivation to take and seek cocaine and fentanyl, relative to continuous access. In this study, we examined the effects of intermittent‐ and continuous‐access self‐administration on heroin intake, patterns of self‐administration and cue‐induced heroin‐seeking, after forced or voluntary abstinence, in male and female rats. We also modelled brain levels of heroin and its active metabolites. Experimental Approach: Rats were trained to self‐administer a palatable solution and then heroin (0.075 mg·kg −1 per inf) either continuously (6 h·day −1 ; 10 days) or intermittently (6 h·day −1 ; 5‐min access every 30‐min; 10 days). Brain levels of heroin and its metabolites were modelled using a pharmacokinetic software. Next, heroin‐seeking was assessed after 1 or 21 abstinence days. Between tests, rats underwent either forced or voluntary abstinence. The oestrous cycle was measured using a vaginal smear test. Key Results: Intermittent access exacerbated heroin self‐administration and was characterized by a burst‐like intake, yielding higher brain peaks of heroin and 6‐monoacetylmorphine concentrations. Moreover, intermittent access increased cue‐induced heroin‐seeking during early, but not late abstinence. Heroin‐seeking was higher in females after intermittent, but not continuous access, and this effect was independent of the oestrous cycle. Conclusions and Implications: Intermittent heroin access in rats resembles critical features of heroin use disorder: a self‐administration pattern characterized by repeated large doses of heroin and higher relapse vulnerability during early abstinence. This has significant implications for refining animal models of substance use disorder and for better understanding of the neuroadaptations responsible for this disorder. LINKED ARTICLES: This article is part of a themed issue on Advances in Opioid Pharmacology at the Time of the Opioid Epidemic. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v180.7/issuetoc